Group Identity and Social Preferences - Chen, Yan; Li, Sherry Xin (American Economic Review, 2009)
We present a laboratory experiment that measures the effects of induced group identity on social preferences. We find that when participants are matched with an ingroup member, they show a 47 percent increase in charity concerns and a 93 percent decrease in envy. Likewise, participants are 19 percent more likely to reward an ingroup match for good behavior, but 13 percent less likely to punish an ingroup match for misbehavior. Furthermore, participants are significantly more likely to choose social-welfare-maximizing actions when matched with an ingroup member. All results are consistent with the hypothesis that participants are more altruistic toward an ingroup match. (JEL C91, D03, Z13)